A study on roles and activities of the Bangladeshi migrant workers in commercialized farming of Cameron Highlands in Malaysia - Karim, A.H.M Zehadul (International Islamic University Malaysia, 2018)
Cameron Highlands, an enchanting mountainous region with steep slopes and hill peaks of Malaysia has an atmospheric support and ecological suitability which allows a group of enthusiastic entrepreneurs with considerable ability for an innovative agriculture in the region. Based on labour-intensive family farming, one conspicuous feature of these farms is that they employ a large number of foreign workers from neighbouring South East Asian and South Asian countries who understand the intricacies of this type of cultivation. The findings show that the entrepreneurs have been able to adapt by interacting and responding properly to the existing eco-environment of Cameron Highlands which has effectually kept alive continuous economic and commercial activities in this region through innovative and sustainable agriculture. The research however, cautions the overuse of chemical fertilizers bearing impact on human health for which it is suggested that chemical technification of cultivation should be minimized; instead, the entrepreneurs should focus more on the pre-existing local skills with labour-intensive organic farming